Значення та структура корпоративної аналітики бізнесу в умовах воєнного стану - Одрехівський, М. В.; Пшик-Ковальська, О. О.; Odrekhivskyi, M. V.; Pshyk-Kovalska, O. O. (Видавництво Львівської політехніки, 2023)
Обґрунтовано необхідність корпоративної аналітики для сучасного бізнесу в умовах воєнного стану. Зокрема, було сформовано такі компетентності аналітика, як: галузеві знання; ефективна комунікація із замовниками; робота із процесами та даними; уміння вчитись; написання бізнес-кейсів. Визначені компетентності аналітика дали змогу виокремити складові елементи корпоративної аналітики, які й сформували її структуру. У результаті встановлено комплексність корпоративної аналітики, що сприятиме цілісності та підвищенню ефективності корпоративного управління.

Analytics for modern business in the conditions of martial law. In particular, it is stated that corporate analytics is aimed at attracting investments, increasing business competitiveness and the efficiency of entrepreneurship, and implementing digital technologies. Corporate analysts play a key role in the implementation of these measures. Corporate analysts are called to help their company or customer carry out effective transformations, offer the most creative and innovative solutions, breaking down the company’s strategy into separate initiatives that make it possible to bring tangible benefits to customers. Therefore, the key skills of such specialists were formed in the article. It was established that corporate analysts should possess a high level of knowledge, develop effective communications, analyze farsightedly, critically, weigh and make conclusions, be open to new knowledge, and be able to present reasonable conclusions of the conducted research in an accessible manner. Such analyst competencies make it possible to distinguish the components of corporate analytics, namely: system analytics, business analytics, financial analytics, HR analytics, information analytics, web analytics and predicative analytics, which in turn is divided into descriptive and prescriptive analytics. These components form the structure of corporate analytics. As a result, it was proposed to interpret corporate analytics as methods and means of systematic observation, collection, processing, systematization and analysis of information for the purpose of evaluating the current and retrospective states of the external and internal environments of enterprises, human resources, the efficiency of business processes, functions, actions and operations, modeling and forecasting their prospective states with the help of information and telecommunication technologies to support the adoption and implementation of optimal management decisions. Prospects for further research will be a detailed analysis of the components of corporate analytics.
The significance and structure of corporate business analytics under the conditions of martial state
Keywords: аналітик; корпоративна аналітика; корпоративне управління; бізнес-аналітика; компетентності; analyst; corporate analytics; corporate management; business analytics; competencies; 330.46; 330.43